Asesmen Pembelajaran Maharah Istima’ Berbasis Aplikasi Kahoot - Fadilatullaila, Ummi; Halifah, Nur; Maksum, M. Syukron; Aminudin (AL-MUTSLA, 2025)
This study aims to identify the Kahoot application that can be used as a digital-based assessment. The objective to be achieved in this study is how the evaluation of Arabic language learning based on digital assessment with the Kahoot application is carried out, this study was conducted using a descriptive qualitative approach. To describe and connect the problems with the theories that have been described, so as to produce solutions for each existing problem. Data collection techniques used observation and questionnaires. The selected research observation was PPBA University of Muhammadiyah Malang. For data analysis, the researcher used the process of presenting data and then drawing conclusions. From the results of student perceptions, it shows that the Kahoot application can be used as a digital assessment in the evaluation of Arabic language learning Maharah Istima'. Based on the results of the questionnaire that has been distributed, the use of the Kahoot application as an interesting application for evaluating Arabic language learning Maharah Istima' received a positive response with an interesting category with a percentage value of 33.3%, responses with an interesting category got a value of 60%, the rest of the responses with an ordinary category got a value of 7%.